A religião institucionalizada no Congresso Nacional: uma análise das frentes parlamentares evangélica e católica e candidaturas de identidade religiosa e o abuso do poder religioso nas Eleições 2018 e 2022 - Lima, Lunara Farias (2023)
The present dissertation arises from the increasingly intertwined relationship betw een religion and politics in the Brazilian scenario. Visualiz ing religion in an institutional ized way in the National Congress, through the Evangelical and Catholic Parliame ntary F ronts and the permissiveness o f candidacies of religious identity, the resea rch turns to the arduous understanding of state secularity and the guarantee of individual fr eedoms, in a Democratic State of Law, which must strive f or isonomy, fairness an d electoral legitimacy, while, equall y, it must combat and sanction the abuse of po wer, among which, the religious one. With the aim of translat ing the pernicious relationship between religion and politics into numbers, the work is b ased on data research, with of ficial documentary exploration of democratic institutions, such as the National Congress and the Superior Electoral Court, as well as bibliographical research, extracted from books and articles published in specialize d magazines. Likewise, the electoral legislation in the country's leg al system and the jurisprudence of the Superior Electoral Court on the abuse of religious power are contemp lated. As a conclusion, it remains verified that the Evangelical and Catholic Parliamentary Fronts make up, resp ectivel y, 42.9% and 33.7% of the National Congress, growing with each passing legislature. Its composition, as it is non party, includes parties of different ideologies, such as the right, center and left, despite the predominance of the firsts. Its capacity for articulation and mobilization in the National Congress means that its proposals have a strong chance of success, as well as blocking thos e that are not in line with its christian political interests. It is questionable whether political pluralism, in act, is plural, as there is a predominance of composition through male people, of sef declared white race and from the Southeast Region of Brazil. Religious identity candid acies follow the same tune as the Evangelical and Catholic Parliamentary Fronts. In addition, it is denoted that secularity should be understood as a “Brazilian se cularism” due to the Brazilian experience, with a precise distinction between the secularity that results from social, political and economic movements, and the secularity that comes from a constitutional formalization. Added to this, the fundamental right to religious freedom has been used, lightly, as a cover for the commission of abuse of religious power that is not yet recognized, by legislation and jurisprudence, as an autonomous modality, making it difficult to apply the appropriate sanction. Thus, me asures need to be taken by democratic institutions to guarantee the fairness, authenticity and legitimacy of the young brazilian democracy.